2022
DOI: 10.3389/ijph.2022.1604797
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Extra-family Social Relationship Between Personality and Depressive Symptoms Among Chinese Adults

Abstract: Objectives: This study aims to explore the associations of personality traits and extra-family social relationship with depressive symptoms among Chinese adults.Methods: A nationally representative sample of 29,810 adults aged 16 and above were selected from 2018 CFPS. Personality and depressive symptoms were measured using CBF-PI-15 and the CES-D8 scale. Extra-family social relationship was assessed through the self-rated evaluation. The multiple regression analysis and the PROCESS macro were used for the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The higher the score, the greater level or intensity of depressive symptoms [58]. CES-D8 has been widely proven to have reliability and validity in measuring depressive symptoms [59][60][61]. The Cronbach's alpha coefficient of depressive symptoms in this study was 0.766.…”
Section: Measurements 221 Depressive Symptomsmentioning
confidence: 54%
“…The higher the score, the greater level or intensity of depressive symptoms [58]. CES-D8 has been widely proven to have reliability and validity in measuring depressive symptoms [59][60][61]. The Cronbach's alpha coefficient of depressive symptoms in this study was 0.766.…”
Section: Measurements 221 Depressive Symptomsmentioning
confidence: 54%
“…Sample items include “I often feel disturbed (Neuroticism)”, “One of my characteristics is doing things logically and orderly (Conscientiousness)”, “I think most people are well-intentioned (Agreeableness)”, “I’m a person who loves to take risks and break the rules (Openness)”, and “I like to go to social and recreational parties (Extraversion)”. With good reliability and validity (such as convergent, discriminant, and criterion-related validity) [ 34 ], the CBF-PI-15 has been widely adopted in previous studies (e.g., [ 36 , 37 ]). The internal consistency values for each subscale were as follows: Neuroticism (0.83), Conscientiousness (0.75), Agreeableness (0.70), Openness (0.88), and Extraversion (0.70).…”
Section: Methodsmentioning
confidence: 99%
“…The mediating effect of social support on the relationship between frailty and depression was observed [ 19 ]. Study also found that extra-family support mediated the association between extraversion and depressive symptoms [ 20 ]. There is a strong association between COPD and depressive symptoms; however, the mediating effect of filial piety, a form of social support, on this association is unknown.…”
Section: Introductionmentioning
confidence: 99%